Drug Resistance in Malaria-in a nutshell - Dipanjan Bhattacharjee,G. Shivaprakash (Journal of Applied Pharmaceutical Science, 2016)
One peek into the history of malaria, shows us that despite many attempts by mankind to counter the development and propagation of malaria, it has always risen back like a ‘phoenix from its ashes’. This has been possible by virtue of the singular ability of the malarial parasite to mutate and evade the actions of various anti-malarial drugs. The emergence of drug resistant malarial parasites by virtue of the various molecular mechanisms, has put the authorities under the cosh and forced the scientists to start generating newer and better anti-malarial drugs. In this review, we have dwelt upon the various molecular mechanisms which have allowed the malaria parasite to develop resistance, as it can serve to educate the scientists in their effort to generate newer anti-malarials.
Keywords: History,Resistance mechanisms,Current status.